Psychometric properties of the Spanish version of the Chalder Fatigue Scale in clinical and general populations - Ceballos-Munuera, Celia; Senín-Calderón, Cristina; Rosales-Becerra, Ángela; Rodríguez-Testal, Juan Francisco (Anales de Psicología / Annals of Psychology, 2024)
Objective: The Chalder Fatigue Scale (CFS) is a brief self-report screening scale for fatigue that is used in Spain but has not been validated for the Spanish population. The aim of this study was to adapt and evaluate the psychometric properties of the Spanish version of the CFS (Sp-CFS). Method: The sample consisted of 3,671 participants (3,190 from the general population and 481 patients), aged 18 to 86 years (M = 28.43; DT = 12.71), 67.6% of whom were women. Psychometric properties of the scale were tested in a cross-sectional design using cross-validation (exploratory and confirmatory factor analysis) and estimation of invariance (sex and clinical condition). Results: A four-factor model (low energy, sleep problems, concentration problems and subjective cognitive dysfunction) rather than an original two-factor model (physical and mental fatigue) provided better indices of goodness of fit to the data. The internal consistency and stability of the scale were excellent. Its convergent validity was supported by its significant association with anxiety, depression, stress, and the positive and negative symptoms of the psychosis spectrum. The instrument did not show significant differences between sexes or clinical conditions, and it discriminated between the general population and the patients, with the latter obtaining significantly greater scores. Conclusions: Sp-CFS is a reliable and valid scale for measuring a transdiagnostic construct such as fatigue in Spanish general and clinical populations.